2004
DOI: 10.1007/s00420-004-0537-y
|View full text |Cite
|
Sign up to set email alerts
|

Risk of health complaints and disabilities among Dutch firefighters

Abstract: Firefighters reported higher physical demands (with the exception of 'sitting') than office workers did. The prevalence rate of certain complaints or disabilities among FFs was higher (knee and ankle complaints and disabilities related to back complaints) or lower (hypertension, stomach, heart, neck, shoulder and arm complaints) than among OWs. The results suggest that exposure to highly biomechanically demanding activities might cause an increased risk of knee and ankle complaints and that exposure to highly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0
7

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 42 publications
1
34
0
7
Order By: Relevance
“…The shift pattern being a stressor is consistent with some previous research where it was attributed to causing physical distress (Bos et al 2004;Murphy et al 2002). In contrast, Litchfield and Hinckley (2016) didn't find such a relationship but found that a different shift pattern (of two days and two nights on and four days off) was associated with a better work-life balance amongst firefighters.…”
Section: Effects Of Stressorssupporting
confidence: 88%
See 1 more Smart Citation
“…The shift pattern being a stressor is consistent with some previous research where it was attributed to causing physical distress (Bos et al 2004;Murphy et al 2002). In contrast, Litchfield and Hinckley (2016) didn't find such a relationship but found that a different shift pattern (of two days and two nights on and four days off) was associated with a better work-life balance amongst firefighters.…”
Section: Effects Of Stressorssupporting
confidence: 88%
“…There are number of incident-related stressors faced by Fire Service personnel that can affect their mental and physical health including time pressure, lack of sleep, fatigue, high stakes decision making, risk of injury to self or death, and exposure to other people's trauma (Bos et al 2004;Murphy et al 2002). The National Institute for Occupational Safety and Health (2004) has attributed an increase in deaths of firefighters to cardiac arrest and high blood pressure (Kales et al 2009), and they are noted to suffer from weakened immune systems, musculoskeletal difficulties, and fatigue (Cohen and Herbert 1996).…”
mentioning
confidence: 99%
“…Kenny, Yardely, Martineau, et al argued that properly trained firefighters aged 40-60 could maintain recommended V O2 max levels [28]. The reason for this correlation could be a decline in training with age rather than age itself, which implies both physical and psychological risks to participants [29,30,31]. According to Lusa, Louhevaara and Kinnunen, physical work and the demand for work capacity remained the same throughout a firefighter's career regardless of age and this should not affect a firefighter's performance [12].…”
Section: Discussionmentioning
confidence: 99%
“…Huang and colleagues carried out a survey on experiences of trouble and injury and subjective evaluation of PPE for Chinese firefighters 16) . Bos and colleagues compared the work demands, health complaints, and disabilities of firefighters to office workers 17) . However, recent surveys on firefighter mobility in relation to PPE were not found.…”
Section: Introductionmentioning
confidence: 99%